TEACHERS’ SUPPORT AND PUPILS’ WRITING STRATEGIES IN A NETWORKED ELEMENTARY-SCHOOL LEARNING ENVIRONMENT INTEGRATING A BLOG - Thériault, Pascale; Allaire, Stéphane; Gagnon, Vincent (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2018)
Although the affective dimension of writing is important and well documented, we know less about how teachers and students are making use of the blog in classrooms to advance specifically cognitive goals connected to writing. It is with this in mind that a case study was carried out to closely document the effect of classroom blogs on the development of writing in 6th grade pupils. The study intended to a) describe the kind of support about writing provided by teachers and b) describe how writing strategies and processes were used by the pupils while they were using the blog. Two teachers and the students in their classrooms participated in our study. Data were collected from classroom observations and interviews. We used Hayes and Flower’s writing processes, elaborated in 27 writing strategies, to analyze the classroom data. The results reveal that teachers focused the most on planning and revising processes. LE SOUTIEN D’ENSEIGNANTS ET LES STRATÉGIES D’ÉCRITURE D’ÉLÈVES DU PRIMAIRE DANS UN ENVIRONNEMENT D’APPRENTISSAGE EN RÉSEAU INTÉGRANT UN BLOGUE Bien que la dimension affective de l’écriture soit importante et bien documentée, peu d’écrits ont étudié comment les enseignants et les élèves font usage d’un blogue pour travailler les aspects cognitifs de l’écriture. C’est avec cette préoccupation en tête que nous avons documenté l’incidence d’un blogue sur le développement de l’écriture d’élèves de 6e année du primaire. Les objectifs de l’étude ont été les suivants: a) décrire le type de soutien à l’écriture fourni par les enseignants et b) décrire comment les processus et les stratégies d’écriture ont été utilisés par les élèves pendant leur usage du blogue. Deux enseignants et leurs élèves ont participé à l’étude. Les données ont été collectées à partir d’entrevues et d’observations en classe. Nous avons utilisé les processus d’écriture de Hayes et Flower, déclinés en 27 stratégies, pour analyser les données. Les résultats indiquent que les enseignants ont mis surtout l’accent sur les processus de planification et de révision.